Modeling the uptake of plug-in vehicles in a heterogeneous car market using a consumer segmentation approach - Brand, C; Cluzel, C; Anable, J (Elsevier, 2017)
There is broad agreement on the need for substantial use of low carbon vectors in the long term in the transport sector. Electrification, via mass market adoption of plug-in vehicles (i.e. battery electric and plug-in hybrid electric vehicles), has emerged as a front runner for road transport across the globe, but there are concerns that the pace and extent implied by many modelling studies is problematic and that assessment of (a) the heterogeneity in the market, (b) other low carbon vectors (e.g. conventional hybrids, hydrogen fuel cell) and (c) life cycle energy and environmental impacts have been relatively neglected. This paper aims to fill these gaps by examining the timing, scale and impacts of the uptake of plug-in vehicles in the heterogeneous UK car market from a consumer perspective. To achieve this aim it (a) brings together a bespoke disaggregated model of the transport-energy-environment system (the UK Transport Carbon Model) with previous work by the authors on heterogeneity in the demand for and supply of plug-in vehicles and (b) applies the improved model to develop future low carbon scenarios that assess the potential impact of different investment pathways and policy approaches to the electrification of cars with the view to meeting the UK’s legally binding carbon budgets to 2050. The results show the importance of accounting for the heterogeneity in and dynamic nature of the car market in terms of new technology adoption by private consumers, so called ‘user choosers’ and fleet managers, as well as accounting for potential effects on wider life cycle emissions resulting from different uptake pathways. It allows an assessment of the effectiveness of different policy instruments, market conditions (vehicle supply, private vs fleet market, vehicle segments) and social factors (consumer awareness, range “anxiety”, perceived charging requirements) on different consumer segments, thus providing more policy-focused conclusions on the likely pathways to high penetration of plug-in vehicles that may be required to meet future carbon and air quality targets.